ANALISA OPTIMASI PEROLEHAN KONDENSAT MENGGUNAKAN SIMULASI UNTUK DRY GAS CYCLING PADA RESERVOIR GAS LAPANGAN âXâ - Yosua, Hendro
One of the techniques used in enhancing the maximum recovery of condensate in the industry practice is dry gas cycling operation. Simulation of direct line injection well is performed in this study to find the incremental of maximum recovery factor value compared to the natural depletion case by gas cycling operations. The recovery incremental values can then be optimized both technically and economically, by analyzing the condensate field development scenarios and their effects on cumulative oil and gas production. Assuming the facility surface constraint is the same for all cases, the optimization is done by analyzing the sensitivity of production management and gas strippng parameters such as injector well distance, gas re-injection fraction, and the value of reservoir pressure maintenance. However, there are differences in the results given for condensate maximum recovery by the reservoir simulation up to 32.9% compared to the study results of Bradley and Pollard. From the analysis of the development scenario, technically it was found that the maximum value of condensate recovery factor is when current injector well at farthest distance from the producer well, but had highest perforation interval and at 60% flow rate re-injection fraction of dry gas. This scenario can provide additional recovery factor up to 11.27%. For the case of reservoir pressure maintenance, optimization obtained at a pressure of 1,700 psia. But, the re-injection fraction and pressure maintenance scenario can not be run in combination because there are differences in consideration for the reservoir. Meanwhile, in economic terms, the largest revenue will be obtained at 10% flow rate re-injection if it does not consider the gas plateau rate during the contract period. Re-injection over 50% on the X Field will hold the gas plateau rate fully 25-years contract period.. The farther the distance of injection well, areal-sweeping efficiency will be optimum for increasing the condensate and gas recovery. Final analysis shows that, condensate recovery is optimized when reservoir pressure stands at optimum liquid condensation pressure at fluid’s phase envelope.